Improving the efficiency of dynamic analysis of the combined simulation model for software with parallelism - Suprunenko, Oksana; Onyshchenko, Borys; Grebenovich, Julia (Eastern-European Journal of Enterprise Technologies, 2023)
Software design uses the set of tools for building and analyzing models which do not allow solving the complex problem of improving the quality of design solutions. This task includes not only the synthesis of the software model with parallelism, the detection and localization of errors for the correction of the model, but also the visual analysis of the model for the synthesis of new or corrected design solutions. The study object is the building and analyzing processes of software models with parallelism. Techniques and a method‘s of synthesis and analysis of the software model with parallelism are proposed, which are based on the combined approach to simulation modelling of the systems with parallelism. The analysis of the software model with parallelism begins at the stage of creating and static analyzing component models. The proposed method provides dynamic analysis of component models and partial model in the process of assembling the complete software model. Building of component models is carried out based on the rules for building PN-models, PN-templates and the principle of structural similarity, while their static properties are checked. The dynamic analysis of the component models of software is carried out using simulation modeling and the method of invariants. In process of the model assembling, the complete model is gradually formed by assembling it from the models of software components, and its dynamic properties are analyzed. In this case, the convolution method, the method of invariants, and simulation modelling are used. Through in-depth dynamic analysis the presented method‘s provides an opportunity to check the static and dynamic properties of the studied models, which ensures an increase in the quality of project solutions at the software design stage. It can be used to reduce the cost of software development, as well as to analyze the developed software to improve the efficiency of support